2009
DOI: 10.1104/pp.109.147280
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Small RNA-Mediated Responses to Phosphate Deficiency in Arabidopsis by Deep Sequencing

Abstract: Recent studies have demonstrated the important role of plant microRNAs (miRNAs) under nutrient deficiencies. In this study, deep sequencing of Arabidopsis (Arabidopsis thaliana) small RNAs was conducted to reveal miRNAs and other small RNAs that were differentially expressed in response to phosphate (Pi) deficiency. About 3.5 million sequence reads corresponding to 0.6 to 1.2 million unique sequence tags from each Pi-sufficient or Pi-deficient root or shoot sample were mapped to the Arabidopsis genome. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
719
4
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(785 citation statements)
references
References 67 publications
57
719
4
5
Order By: Relevance
“…The presence of tRNA-derived RNA fragments (Lee et al 2009) has been detected also in plants Hackenberg et al 2012;Hsieh et al 2009) as well as their putative target genes (Guilherme Loss-…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tRNA-derived RNA fragments (Lee et al 2009) has been detected also in plants Hackenberg et al 2012;Hsieh et al 2009) as well as their putative target genes (Guilherme Loss-…”
Section: Discussionmentioning
confidence: 99%
“…The existence of miRNAdependent pathway in distinct aspects of Pi homeostasis in these two species may suggest a species-specific pathway where many unannotated transcripts may play significant roles. It has been reported that miR2111 may target the E3 ligase gene and a calcineurin-like phosphoesterase gene under −P stress (Hsieh et al 2009). Additionally, miRNAs such as miR169, miR395, and miR398, which respond to various nutritional stresses, were also downregulated in response to Pi stress (Hsieh et al 2009).…”
Section: Identification Of Responsive Non-protein Coding Transcriptsmentioning
confidence: 99%
“…It has been reported that miR2111 may target the E3 ligase gene and a calcineurin-like phosphoesterase gene under −P stress (Hsieh et al 2009). Additionally, miRNAs such as miR169, miR395, and miR398, which respond to various nutritional stresses, were also downregulated in response to Pi stress (Hsieh et al 2009). Therefore, some of the unannotated transcripts detected here including nonprotein coding transcripts and small RNAs may have important functions in the signaling of plant root responses to changing Pi concentrations and the coordination of homeostatic pathways of Pi and other nutrients.…”
Section: Identification Of Responsive Non-protein Coding Transcriptsmentioning
confidence: 99%
“…genes, and these analyses have also contributed to our understanding of the global response to Pi deficiency (23)(24)(25).…”
mentioning
confidence: 99%